2014
DOI: 10.1161/circheartfailure.113.000937
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vagal Nerve Stimulation on Left Atrial Structure and Function in a Canine High-Rate Pacing Model

Abstract: Background Cervical vagal nerve stimulation (VNS) can improve left ventricular dysfunction in the setting of heart failure (HF). However, little is known about the impact of VNS on left atrial (LA) function. The aim of this study was to compare LA mechanics and histology between control and VNS-treated animals during HF development. Methods and Results Fifteen mongrel dogs were randomized into control (n=7) and VNS (n=8) groups. All dogs underwent 8 weeks of high-rate ventricular pacing (at 220bpm for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
2
14
0
1
Order By: Relevance
“…The results showed that vagal stimulation markedly attenuated left ventricular dysfunction, prevented left ventricular dilation and positively influenced the apoptotic, inflammatory and NO biomarkers. Vagal stimulation therapy has also been shown to favourably affect the left atrial function and structure in heart failure dogs (Kusunose et al ., ). Our previous studies have suggested that vagal stimulation improved cardiac pump function, reduced infarct size and decreased serum myocardial enzyme activities in a rat model of acute myocardial infarction (Kong et al ., 2011; 2012a).…”
Section: New Therapeutic Options Targeting Modulation Of Vagal Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that vagal stimulation markedly attenuated left ventricular dysfunction, prevented left ventricular dilation and positively influenced the apoptotic, inflammatory and NO biomarkers. Vagal stimulation therapy has also been shown to favourably affect the left atrial function and structure in heart failure dogs (Kusunose et al ., ). Our previous studies have suggested that vagal stimulation improved cardiac pump function, reduced infarct size and decreased serum myocardial enzyme activities in a rat model of acute myocardial infarction (Kong et al ., 2011; 2012a).…”
Section: New Therapeutic Options Targeting Modulation Of Vagal Activitymentioning
confidence: 97%
“…Vagal stimulation therapy has also been shown to favourably affect the left atrial function and structure in heart failure dogs (Kusunose et al, 2014). Our previous studies have suggested that vagal stimulation improved cardiac pump function, reduced infarct size and decreased serum myocardial enzyme activities in a rat model of acute myocardial infarction .…”
Section: Vagal Stimulation Ach and Ach Receptor Activationmentioning
confidence: 98%
“…VNS has also been investigated in animal models of chronic heart failure, a condition characterised by a sustained increase in sympathetic drive and a concurrent withdrawal of parasympathetic activity (Triposkiadis et al, 2009). A sustained improvement in cardiac function and heart failure symptoms has been demonstrated as a result of VNS (Hamann et al, 2013;Kusunose et al, 2014;Li et al, 2004;Sabbah et al, 2011;Zhang et al, 2009). …”
Section: Anatomy Of the Auricular Branch Of The Vagus Nervementioning
confidence: 99%
“…In addition to suppressing sympathetic outflow, vagal nerve and epicardial ganglionated plexi stimulations may be anti-inflammatory 100, 143, 144 and may improve LA function and suppress the development of LA fibrosis. 145 Renal sympathetic denervation may control AF through modification of the atrial substrates. 6 These findings suggest that neuromodulation may achieve its therapeutic effects in part by causing beneficial structural and functional remodeling in the heart.…”
Section: Neuromodulation As a Therapeutic Approachmentioning
confidence: 99%